2022
DOI: 10.3390/ani12040513
|View full text |Cite
|
Sign up to set email alerts
|

Lower Reproductive Rate and Lamb Survival Contribute to Lower Lamb Marking Rate in Maiden Ewes Compared to Multiparous Ewes

Abstract: Suboptimal reproductive performance of maiden (primiparous) ewes remains a source of inefficiency for the Australian sheep industry. However, the extent and causes of the poorer reproductive performance of maiden ewes on Australian sheep farms are not well understood. Here, we show the reproductive performance of maiden ewes relative to their multiparous counterparts on the same farms across Australia using a cohort survey. The difference in marking rate for non-Merino maiden ewe lambs compared to multiparous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…It is accepted that the reproductive performance of ewe lambs is consistently lower than that of both 2 year old and mature ewes [ 10 ]. A recent survey of farmers in Australia found that the reported reproductive rate of ewe lambs and mature ewes differed by 50% [ 16 ]. The lower number of lambs weaned per ewe lamb presented for breeding is due to a number of factors ( Table 1 ).…”
Section: Comparison Of Reproductive Traits Of Ewe Lambs and Mature Ewesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accepted that the reproductive performance of ewe lambs is consistently lower than that of both 2 year old and mature ewes [ 10 ]. A recent survey of farmers in Australia found that the reported reproductive rate of ewe lambs and mature ewes differed by 50% [ 16 ]. The lower number of lambs weaned per ewe lamb presented for breeding is due to a number of factors ( Table 1 ).…”
Section: Comparison Of Reproductive Traits Of Ewe Lambs and Mature Ewesmentioning
confidence: 99%
“…Variation exists among breeds and genotypes with regard to timing and live weight at puberty, proportion of ewe lambs displaying estrus (i.e., puberty achievement) within season, length of reproductive season, pregnancy and reproductive rates, and lambing percentage [ 10 , 16 , 81 ]. Therefore, farmers have scope to select breeds or genotypes most suitable to be bred as ewe lambs.…”
Section: Factors Affecting Ewe Lamb Performance Prior To and During B...mentioning
confidence: 99%
“…Semen traits could similarly play a role in influencing litter size in livestock species, including sheep which, in turn, may influence the profitability of sheep enterprises. Given maiden ewes have significant abortion and lamb mortality rates compared to multiparous ewes [ 12 , 13 ], improving semen quality and quantity traits through selective breeding may also afford opportunities to improve maiden ewe reproduction rates. As such, every ejaculate collected should be routinely assessed to determine quality prior to use in artificial breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, the causes of foetal and lamb losses between pregnancy diagnosis in mid‐pregnancy and lamb marking for maiden ewes are not well studied. Furthermore, it is not clear whether infectious diseases are an important contributor to the poorer reproductive performance reported for maidens compared to multiparous ewes 5–8 …”
mentioning
confidence: 99%
“…Furthermore, it is not clear whether infectious diseases are an important contributor to the poorer reproductive performance reported for maidens compared to multiparous ewes. [5][6][7][8] Ovine campylobacteriosis caused by Campylobacter fetus or Campylobacter jejuni is one of the most frequently diagnosed causes of ovine abortion in Australia. 9,10 Transmission occurs via ingestion of feed and water contaminated by faeces or aborted material, with no evidence of venereal spread in sheep.…”
mentioning
confidence: 99%